Case Report: Rapid Desensitization to Ocrelizumab for Multiple Sclerosis Is Effective and Safe - Aun, Marcelo Vivolo; Freua, Fernando; Marussi, Victor Hugo Rocha; Giavina-Bianchi, Pedro (Frontiers in Immunology, 2022)
Monoclonal antibodies have become a mainstay of treatment for many inflammatory diseases and malignancies. Multiple sclerosis is a chronic inflammatory, demyelinating, and neurodegenerative disease of the central nervous system and a common cause of disability in young adults. Ocrelizumab is a recombinant humanized monoclonal antibody that targets CD20-positive B cells and has been approved in the treatment of multiple sclerosis. Although considered safe, more than 30% of patients treated with Ocrelizumab developed infusion-related reactions, mostly regarded as mild. When severe, they can lead to a definite suspension of that drug. We present a case report of Ocrelizumab desensitization in a female patient who presented an immediate hypersensitivity reaction (urticaria and angioedema) during the first Ocrelizumab infusion. Although mechanisms involved in the response were not elucidated, the procedure occurred uneventfully and permitted first-line multiple sclerosis treatment maintenances. Desensitization should be considered a safe therapeutic option in patients with immediate hypersensitivity reactions to Ocrelizumab.